2022
DOI: 10.1002/mde.3629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of business innovation on future employment in Nigeria

Abstract: As the global economy continues to recover from COVID-19 shocks, slower growth and not enough jobs to commensurate the growing labour force are observed. In line with SGD-8, promoting decent work, sustainable economic growth, higher levels of productivity and technological innovation, this study argues that encouraging entrepreneurship for job creation is key to securing future employment. The study applied the Propensity Score Matching (PSM) to carry out the impact analysis. In addition, the study employed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…improvement in society at large) rather than by their ability to provide services to the group they represent (i.e. concentrating on outputs) (Osabohien et al , 2022b). For their similarity, both social entrepreneurs and for-profit entrepreneurs look for market gaps to fill with a new venture to serve an underserved market.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…improvement in society at large) rather than by their ability to provide services to the group they represent (i.e. concentrating on outputs) (Osabohien et al , 2022b). For their similarity, both social entrepreneurs and for-profit entrepreneurs look for market gaps to fill with a new venture to serve an underserved market.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This is because it bridges information asymmetry in the labour market. Similarly, Osabohien et al (2022aOsabohien et al ( , 2022b found that social entrepreneurship and business innovation are significant drivers of future employment. In another study, Matthew et al (2020) found that enabling environment, infrastructure and access to ICT tools are crucial for business operations.…”
Section: Introductionmentioning
confidence: 98%
“…ICT has given people control over their home thermostats, enable them to exercise control over their heartbeats, monitor their diets, and have groceries delivered to their doorsteps (Garcia‐Murillo, 2017). ICT has also strengthened the capacities of entrepreneurship (Osabohien et al, 2022). For instance, entrepreneurs can easily monitor their sales and production, detect failures in production and of course automate many tasks that were previously undertaken manually, which has resulted in a decline in the cost of production (Osabohien et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…ICT has also strengthened the capacities of entrepreneurship (Osabohien et al, 2022). For instance, entrepreneurs can easily monitor their sales and production, detect failures in production and of course automate many tasks that were previously undertaken manually, which has resulted in a decline in the cost of production (Osabohien et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation